Real-time analysis of dynamic compartmentalized GSH redox shifts and H2O2 availability in undifferentiated and differentiated cells - Davies, Brandon M.; Katayama, Jenna K.; Monsivais, Joshua E.; Adams, James R.; Dilts, Miriam E.; Eberting, Arielle L.; Hansen, Jason M. (Biochimica et biophysica acta. General subjects, 2023)
Glutathione (GSH) is the most abundant, small biothiol antioxidant. GSH redox state (Eh) supports developmental processes, yet with disrupted GSH Eh, poor developmental outcomes may occur. The role of subcellular, compartmentalized redox environments in the context of redox regulation of differentiation is not well understood. Here, using the P19 neurogenesis model of cellular differentiation, kinetics of subcellular H2O2 availability and GSH Eh were evaluated following oxidant exposure. Stably transfected P19 cell lines expressing H2O2 availability or GSH Eh sensors, Orp1-roGFP or Grx1-roGFP, respectively, targeted to the cytosol, mitochondria, or nucleus were used. Dynamic, compartmentalized changes in H2O2 availability and GSH Eh were measured via spectrophotometric and confocal microscopy over 120 min following treatment with H2O2 (100 μM) in both differentiated and undifferentiated cells. Generally, treated undifferentiated cells showed a greater degree and duration of both H2O2 availability and GSH Eh disruption than differentiated neurons. In treated undifferentiated cells, H2O2 availability was similar in all compartments. Interestingly, in treated undifferentiated cells, mitochondrial GSH Eh was most affected in both the initial oxidation and the rebound kinetics compared to other compartments. Pretreatment with an Nrf2 inducer prevented H2O2-induced effects in all compartments of undifferentiated cells. Disruption of redox-sensitive developmental pathways is likely stage specific, where cells that are less differentiated and/or are actively differentiating are most affected. Undifferentiated cells are more susceptible to oxidant-induced redox dysregulation but are protected by chemicals that induce Nrf2. This may preserve developmental programs and diminish the potential for poor developmental outcomes. •Undifferentiated cells are more prone to redox shifts than differentiated cells.•Differentiated cells have higher glutathione and antioxidant gene expression.•A chemical inducer of Nrf2 prevents oxidizing shifts in undifferentiated cells.•roGFP provides real-time, compartmentalized measurements of redox shifts in neurons.